Integrating Cognitive Behavioral Therapy and Exercises: Comprehensive Strategies for Cyclic Mastalgia - S. F. Mariyam Farzana; V. Sunil Kumar; Rajapreethi R; V. M. Vinodhini; P. Venkatraman; Suresh T.N.; Ashish Mathew A; Preethi M; Budireddi Udaya Rasi (An Overview of Disease and Health Research Vol. 2, 2025)
Cyclic mastalgia, commonly referred to as cyclical breast pain, is a widespread condition that affects a significant number of women worldwide. The aim of this review is to evaluate the effectiveness of an integrated intervention combining Cognitive Behavioral Therapy (CBT) and physical exercise in reducing the severity, frequency, and psychological impact of cyclic mastalgia in women. The physiology of cyclic mastalgia is attributed to a complex interplay of physical and psychological stressors, as well as dietary irregularities. These factors can lead to reduced energy intake, resulting in a drop in total triiodothyronine (TT3) levels and subsequent hypothyroidism. Low TT3 levels trigger the release of thyrotropin-releasing hormone (TRH) and thyroid-stimulating hormone (TSH), which inhibit dopamine release and increase prolactin production. Elevated prolactin levels disrupt the hypothalamic-pituitary-ovarian (HPO) axis, leading to luteal phase malfunction. Various intrinsic and extrinsic factors contribute to breast pain, including inadequate breast hygiene, wearing the wrong bra size, and certain medications such as hormonal pills, specific antidepressants, and antihistamines. Research suggests that engaging in regular physical exercise can reduce the severity and duration of mastalgia during the luteal phase. Despite the benefits, many women with mastalgia lead inactive lives, underscoring the need to promote regular physical activity as a therapeutic approach. Physical activity lowers serum aldosterone levels, triggering sodium and water reabsorption and alleviating physical symptoms. Recent evidence highlights the effectiveness of various forms of cognitive behavioral therapy (CBT), including mindfulness-based intervention, dialectical behavior therapy, rational emotive behavior therapy, acceptance and commitment therapy, and behavioral activation therapy for depression. Mindfulness-based intervention focuses on training physical, cognitive, and emotional sensations, as well as attentional processes. The protocol includes breath awareness, body scans, and mindful movement, which limits physical capability. This chapter concludes that Cyclic mastalgia is closely linked to physical activity and psychological parameters. Developing a comprehensive protocol that includes exercise, diet, and psychological interventions can significantly reduce mastalgia symptoms and promote a healthy lifestyle among women.